The Correlation Analysis of Islamic Education (PAI) Learning Outcomes with Religious Tolerance at Universitas Pendidikan Indonesia (UPI) - Hasan Albana; Abas Asyafah; Munawar Rahmat (Universitas Islam Negeri Sunan Kalijaga, 2019)
This study is motivated by the rampant cases and the spread of intolerant and radical understanding. The cases of intolerance and radicalization even occur to students who should possess a tolerant religious understanding and not get caught up in the indoctrination of religious violence. This study aims to analyze the correlation between PAI learning outcomes and religious tolerance. It applies a causal design and quantitative approach with survey method. The population of UPI Bumi Siliwangi is 24.340 students. The data is collected by utilizing probality sampling technique (cluster sampling). There are 344 respondents and questionnaires are served as the research instrument. Then, the data is analyzed by using descriptive and inferential analysis with the assistance of SPSS. The results of this study indicate that the learning outcomes of UPI students mostly get A is at the level of 45,9%. Religious tolerance of UPI students is generally at the most tolerant level of 61,63%. Tolerance to other religions is highest at the tolerant level of 60,17. Tolerance to the same religion but with different understanding, in this case is minority mazhab, is mostly tend to be intolerant level of 47,67%. Tolerance to the state and government, is mostly at the tolerant level of 38,66%. This study finds that there is no significant correlation between PAI learning outcomes and religious tolerance among the UPI students.